Millimeter Wave Fabry-Perot Resonator Antenna Fed by CPW with High Gain and Broadband - Xue-Xia Yang; Guan-Nan Tan; Bing Han; Hai-Gao Xue (International Journal of Antennas and Propagation)
A novel millimeter wave coplanar waveguide (CPW) fed Fabry-Perot (F-P) antenna with high gain, broad bandwidth, and low profile is reported. The partially reflective surface (PRS) and the ground form the F-P resonator cavity, which is filled with the same dielectric substrate. A dual rhombic slot loop on the ground acts as the primary feeding antenna, which is fed by the CPW and has broad bandwidth. In order to improve the antenna gain, metal vias are inserted surrounding the F-P cavity. A CPW-to-microstrip transition is designed to measure the performances of the antenna and extend the applications. The measured impedance bandwidth of S11 less than −10 dB is from 34 to 37.7 GHz (10.5%), and the gain is 15.4 dBi at the center frequency of 35 GHz with a 3 dB gain bandwidth of 7.1%. This performance of the antenna shows a tradeoff among gain, bandwidth, and profile.